Overcoming Gender Disadvantages. Social Policy Analysis of urban middle-class women in Colombia (2013)
The World Bank Report 2012 starts with this statement: “Gender equality matters in itself and it matters for development because, in today’s globalized worlds, countries that use the skills and talents of their women would have an advantage over those which do not use it.” With the frame that suggest that gender equality matters, this paper describes some policy alternatives oriented to overcome gender disadvantages in the formal labor market incorporation of the urban middle class women in Colombia. On balance, the final recommendation suggest that it is desirable to adopt policy alternatives as Community Centers, which are programs oriented to a social redistribution of the domestic work as a way to encourage women participation in the formal labor market with the social support of the members of their own community.